2017
DOI: 10.1093/mnras/stx605
|View full text |Cite
|
Sign up to set email alerts
|

ZFIRE: using Hα equivalent widths to investigate the in situ initial mass function at z ∼ 2

Abstract: We use the ZFIRE a survey to investigate the high mass slope of the initial mass function (IMF) for a mass-complete (log 10 (M * /M ) ∼ 9.3) sample of 102 star-forming galaxies at z ∼ 2 using their Hα equivalent widths (Hα-EW) and rest frame optical colours. We compare dust-corrected Hα-EW distributions with predictions of star-formation histories (SFH) from PEGASE.2 and Starburst99 synthetic stellar population models. We find an excess of high Hα-EW galaxies that are up to 0.3-0.5 dex above the model-predicte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 166 publications
(322 reference statements)
4
45
1
Order By: Relevance
“…As for the ionizing fluxes, this relation does not evolve with redshift for the simulated galaxies, but shifts to higher Σ SFR,Salp , making the average high-mass slope shallower in high-z star-forming galaxies. These slopes are shallower than those found for the z ≈ 2 observations by Nanayakkara et al (2017), for which high-mass IMF slopes of ≈ −2 may be needed to explain their Hα EWs. Zhang et al (2018) recently concluded that high-mass IMF slopes as shallow as −2.1 would be required to explain the 13 CO/C 18 O ratios observed in z ≈ 2 − 3 submillimetre galaxies, which is also steeper than predicted by HiM-50.…”
Section: Redshift Dependence Of the Imfcontrasting
confidence: 63%
See 2 more Smart Citations
“…As for the ionizing fluxes, this relation does not evolve with redshift for the simulated galaxies, but shifts to higher Σ SFR,Salp , making the average high-mass slope shallower in high-z star-forming galaxies. These slopes are shallower than those found for the z ≈ 2 observations by Nanayakkara et al (2017), for which high-mass IMF slopes of ≈ −2 may be needed to explain their Hα EWs. Zhang et al (2018) recently concluded that high-mass IMF slopes as shallow as −2.1 would be required to explain the 13 CO/C 18 O ratios observed in z ≈ 2 − 3 submillimetre galaxies, which is also steeper than predicted by HiM-50.…”
Section: Redshift Dependence Of the Imfcontrasting
confidence: 63%
“…Nanayakkara et al 2017;Zhang et al 2018). In particular, Nanayakkara et al (2017) find that the enhanced Hα equivalent widths (EW) of z ≈ 2 galaxies could be explained with an IMF slope shallower than (under our IMF definition) −2.0. To compare with their data, we compute the ratio of ionizing flux to the SDSS r-band flux, fion/fr, for our simulated galaxies, where fion is the flux of photons with λ < 912 • A, and is a proxy for the Hα flux (Shivaei et al 2018).…”
Section: Redshift Dependence Of the Imfmentioning
confidence: 70%
See 1 more Smart Citation
“…Also we note in closing that more exotic possibilities such as a top-heavy IMF in high Σ SFR environment (e.g. Nanayakkara et al 2017) could reduce SFR and thus flatten out the redshift evolution of t dep ; more work to investigate this possibility could be informative. Finally, as stated above, maps of gas in turbulent disk galaxies will be crucial to determine how pressure may be impacting the properties of massive star forming clusters (as described in Elmegreen & Efremov 1997).…”
Section: Discussionmentioning
confidence: 87%
“…They found no signature corresponding to the significant bursts of star formation that would be seen if stochastic SFHs were the dominant effect. Subsequently, Nanayakkara et al (2017), too, demonstrated quantitatively that stochastic star formation histories could not explain their measurements, in a sample at much higher redshift. Gunawardhana et al (2011) further demonstrate that the result is robust to the implementation of dust correction and choice of population synthesis model.…”
Section: Star Forming Galaxiesmentioning
confidence: 99%